Responsible Leadership and Affective Organizational Commitment: The Mediating Effect of Corporate Social Responsibility - Piñeros Espinosa, Rafael Alejandro (Frontiers in Psychology, 2022)
Organizations and their leaders are challenged to assume a responsible behavior given the increase of corporate scandals and the deterioration of employee commitment. However relatively few studies have investigated the impact of responsible leadership on employee commitment and the effect of corporate social responsibility in this relationship. Using the Social Identity Theory this article examined the mediating effect of corporate social responsibility practices in the relationship between responsible leadership and affective organizational commitment. Data collection was done through a paper survey completed by 309 full-time Colombian employees. Structural equation modelling was used to analyze the data. The results showed that corporate social responsibility fully mediated the influence of responsible leadership on affective organizational commitment. Thus, responsible leadership is an effective mechanism to develop corporate social responsibility practices that in turn increase the levels of affective organizational commitment of employees.